Pengaruh pelatihan online dan motivasi kerja terhadap produktivitas kerja karyawan : Pelatihan Online, Motivasi Kerja terhadap Produktivitas Kerja - Oktaviana, Fransisca Bella; Wardoyo, Dewie Tri Wijayati (Universitas Negeri Surabaya, 2024)
This research aims to determine the effect of online training and work motivation on employee work productivity. This research uses quantitative research with a sampling method using a saturated sampling technique with a total of 40 BPJS Ketenagakerjaan Surabaya respondents. The primary and secondary data sources used in this research are primary and secondary. In this study, data was collected using a questionnaire. The analysis technique used was multiple linear regression techniques using Statistical Product and Service Solutions (SPSS) software version 25. The research results found that online training did not have a significant effect on work productivity. This shows that whether the training is good or bad, it will not impact employee work productivity. Meanwhile, work motivation has a significant positive influence on employee work productivity. This shows that employee work productivity increases or vice versa if work motivation increases. The implications of this research include the need for online training and appropriate work motivation to impact employee efficiency and effectiveness in increasing their work productivity.